Expression of Simian Immunodeficiency Virus nef in Immune Cells of Transgenic Mice Leads to a Severe AIDS-Like Disease - Simard, Marie-Chantal (American Society for Microbiology, 2002)
In order to study the functions of simian immunodeficiency virus (SIV) Nef in vivo in a small-animal model, we constructed transgenic (Tg) mice expressing the SIV(mac)239 nef gene in the natural target cells of the virus under the control of the human CD4 gene promoter (CD4C). These CD4C/SHIV-nef(SIV) Tg mice develop a severe AIDS-like disease, with manifestations including premature death, failure to thrive or weight loss, wasting, thymic atrophy, an especially low number of peripheral CD8(+) T cells as well as a low number of peripheral CD4(+) T cells, diarrhea, splenomegaly, and kidney (interstitial nephritis, segmental glomerulosclerosis), lung (lymphocytic interstitial pneumonitis), and heart disease. In addition, these Tg mice fail to mount a class-switched antibody response after immunization with ovalbumin, they produce anti-DNA autoantibodies, and some of them develop Pneumocystis carinii lung infections. All these results suggest a generalized Nef-induced immunodeficiency. The low numbers of peripheral CD8(+) and CD4(+) T cells are likely to reflect a thymic defect and may be similar to the DiGeorge-like “thymic defect” immunophenotype described for a subgroup of human immunodeficiency virus type 1-infected children. Therefore, it appears that SIV Nef alone expressed in mice, in appropriate cell types and at sufficient levels, can elicit many of the phenotypes of simian and human AIDS. These Tg mice should be instrumental in studying the pathogenesis of SIV Nef-induced phenotypes.